Evaluation of Thermal Behavior of the Skeleton in a Green Building with the Aid of TABS - Muramatsu Hiroshi; Nobe Tatsuo (E3S Web of Conferences, 2019)
In this study, an office building in Japan that incorporates energy-saving features and environmental technologies was investigated. This office building features a green façade, natural ventilation, a concrete slab with no suspended ceilings, and thermo-active building systems. Two airconditioning systems were installed in this building—a ceiling radiation air-conditioning system and a whole floor-blow off air conditioning system. In addition, a natural ventilation system was installed. We surveyed the heat flux of the ceiling surface and indoor thermal environment of this building from 2015 through 2016. The ceiling using the heat storage amount of concrete maintains a constant temperature in the workplace during as well as after office hours. We also performed detailed measurements of the heat flux of the ceiling surface and indoor thermal environment in the summer of 2017. The results showed that the ceiling radiation air-conditioning system provided a stable thermal environment. Furthermore, we report that making use of the thermal behavior of the skeleton improved the operation of the ceiling radiation airconditioning system.